THE IMPLEMENTATION OF KNOW-WANT-LEARNED STRATEGY TO IMPROVE THE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT MTSS INSAN CITA MEDAN - Fathia, Annisa (BRIGHT VISION Journal of Language and Education, 2022)
This research was aimed to find out the impact of using Know-Want-Learned strategy in improving the students’ reading comprehension. The subject of this research was the ninth grade students of MTsS Insan Cita Medan in academic year of 2020/2021 which consisted of 44 students. This research was conducted by using classroom action research, which used two cycles. Each of them consists of planning, acting, observing, and reflecting. The data were obtained through quantitative and qualitative data. The quantitative data was obtained from tests including pre-test, post-test I, and post-test II. While qualitative data was obtained from interview and observation sheet. The result of the data analysis showed that there was an improvement on the students’ reading achievement from each cycle. It was shown from the students’ mean score in pre-test was 57,8 increased to 70,4 in post-test I and increased to 80,5 in post-test II. In the pre-test there were 18,2% (8 of 44 students) who got score  >  75. In the post-test I, there were 45,4% (20 of 44 students) who got score  >  75. In the post-test II, there were 88,6% (39 of 44 students) who got score  >  75. For the hypothesis testing used t-test formula, the result of t-test was tobserved (10,30) > ttable (2,018). Thus,  alternative hypothesis  (Ha) could  be accepted. Based  on  the finding,  alternative hypothesis  (Ha)  saying  that  K-W-L  strategy  could  improve  the  students’  reading comprehension in narrative text.